Mutational analysis in X-linked spondyloepiphyseal dysplasia tarda. - Christie, P; Curley, A; Nesbit, M; Chapman, C; Genet, S; Harper, P; Keeling, S; Wilkie, A; Winter, R; Thakker, R (2001)
Spondyloepiphyseal dysplasia tarda (SEDT) is an X-linked recessive disorder characterized by short stature due to defective growth of the vertebral bodies. In addition, deformities of the femoral heads result in early onset secondary osteoarthritis of the hips. The disorder affects males only with heterozygous female carriers showing no consistent abnormalities. The gene causing SEDT, which is located on Xp22.12-p22.31, consists of 6 exons of which only exons 3, 4, 5, and 6 are translated to yield an 140 amino acid protein, referred to as SEDLIN. SEDLIN mutations have been observed in SEDT patients, and we have undertaken studies to characterize such mutations in four unrelated SEDT kindreds by DNA sequence analysis. We identified two nonsense and two intragenic deletional frameshift mutations. The nonsense mutations occurred in exons 4 (TGG-->TGA, Trp70Stop) and 6 (CGA-->TGA, Arg122Stop). Both of the intragenic deletions, which were approximately 750 bp and 1300-1445 bp in size, involved intron 5 and part of exon 6 and resulted in frameshifts that lead to premature termination (Stop) signals. Thus, all four mutations are predicted to result in truncated proteins. The results of our study expand the spectrum of SEDLIN mutations associated with SEDT, and this will help to elucidate further the role of this novel protein in the etiology of this form of osteochondrodysplasia.